Determinants of Return on Assets in Sharia Commercial Banks: The Moderating Role of Non-Performing Financing - Aulia Nurriski; Putri Rizkiyah; Afsana Yesmin (Journal of Applied Accounting and Sustainable Finance, 2026)
Purpose – This study aims to obtain empirical evidence on the influence of the Islamicity Performance Index (proxied by Profit-Sharing Ratio), Intellectual Capital, and Operational Efficiency Ratio on Return on Assets (ROA), with Non-Performing Financing as a moderating variable. This investigation is particularly relevant in the 2022–2024 period, which represents an era of post-pandemic recovery and accelerated spin-offs of Islamic banking units in Indonesia. Design/methodology/approach – This study employs a quantitative research approach using secondary data. The population consists of 14 Sharia Commercial Banks listed by the Financial Services Authority (OJK) in Indonesia during the period 2022–2024. The sample includes 11 Sharia Commercial Banks selected based on purposive sampling criteria, resulting in 33 observations. The analysis technique used to test the hypothesis is multiple regression analysis and moderation interaction regression using EViews 9 software.         Findings – The results show that the Islamicity Performance Index has a negative and statistically significant effect on ROA, indicating that profit-sharing-based financing has not yet translated into higher short-term profitability during the spin-off era. Intellectual Capital and Operational Efficiency Ratio exhibit negative but statistically insignificant effects on ROA, suggesting that internal resource optimization remains uneven across Sharia banks. Non-Performing Financing has a negative and statistically insignificant direct effect on ROA; however, it significantly strengthens the relationship between the Islamicity Performance Index and ROA. This finding indicates that financing risk plays a critical role in shaping the effectiveness of Sharia-based financing structures on bank profitability, particularly in periods of structural transformation. Research limitations/implications – This study is limited to Sharia Commercial Banks in Indonesia over the 2022–2024 period and relies solely on secondary data. Practically, the findings highlight the importance for Islamic bank management to integrate profit-sharing strategies with robust financing risk control. From a policy perspective, the results provide relevant insights for the Financial Services Authority (OJK) in designing supervisory frameworks that balance Sharia compliance, risk management, and profitability sustainability in the spin-off era. JEL: M41, G21, G32